Subsurface Geotechnical Competence Evaluation Using Geoelectric Sounding and Direct Cone Penetrometer Test at Plural Garden Estate, Ilaramokin Southwestern Nigeria - Igbagbo Adedotun Adeyemo; Andrew Ifeoluwa Afolayan; Bisola Stella Boluwade; Samuel Kayode Alabi (MO.RI Publishing, 2023)
In order to evaluate the geotechnical competence of the subsurface soil materials at Plural Garden Estate, Ilaramokin Southwestern Nigeria, geotechnical investigations involving geoelectric sounding and Direct Cone Penetrometer Test (DCPT) was carried out in the estate. A total of 27 VES points and 8 DCPT points were occupied across the study area. A, H, K, Q and KH are the five sounding curve types delineated in the area. Resistivity values of the top soil, weathered layer, fractured layer and fresh bedrock vary from 65-864, 156-1698, 28-217, 433-12167 ohm-m respectively, while their thicknesses vary from 0.7-3.7, 2.4-10.5 and 6.3-40.1 m in the upper three layers respectively. The geoelectric sounding results were presented as depth slices at depths of 0.5, 0.75, 1.0 and 2.0 m competency maps. Larger part (70 to 80 %) of the surfaces (1.0 and 2.0 m) considered in the study area are characterized as moderate to high competent. The depth slice iso-resistivity maps indicated that geotechnical competence increases with depth within the shallow depths considered (0.5, 0.75, 1.0 and 2.0 m). Geotechnical test involving DCPT were done at common depth of 1.0 m to validate the 1.0 m competency map. The DCPT agreed with the geoelectrical derived 1.0 m depth slice competence map. Some zones suspected to be very low and low competence were revealed to be competent based on DCPT suggesting that the low resistivity may be due to the presence of non-plastic clay and moisture.